Foreign Direct Investment and Economic Growth in Sub-Saharan Africa: The Role of Technology - Kotey, R.A. (University Of Ghana, 2017)
This study sought to assess the economic impact of FDI on economic growth, factoring in technology as an absorptive capacity. To do that, we sampled 43 countries in Sub-Saharan Africa (SSA) over a 19-year period (from 1990 to 2008). We employed a Fixed Effects (FE) regression model. Studies have shown that the effect of FDI on economic growth is not always positive in developing regions; certain characteristics must exit to absorb the effects of FDI. We employ technology as an abortive capacity and interact it with FDI to find its effect on economic growth. We found that FDI had a negative and significant effect on GDP, which is our proxy for economic growth. However when we interact FDI and technology, the relationship is positive and significant. Meaning countries with technology are able to absorb more from FDI. We found also that countries with high technology are able to absorb more from FDI than countries with low technology.
Keywords: economic impact of FDI on economic growth; technology; economic growth.